Atmospheric circulation and sea surface temperature anomalies during the dry summers of 2001/02, 2002/03 and 2003/04 in Southern Africa - Mehari, Michael Futwi (Department of Oceanography, 2024)
Drought is a phenomenon associated with the lack or shortage of water. It means less than normal or no water is available. It primarily originates from lack of precipitation. Lack of precipitation leads to depletion of storage of I. soil moisture that results in dry land crop failure and dying-off grazing and other vegetations, II. of ground water, which results in drying up of springs, streams and boreholes and Ill. of water in man-made reservoirs, which results in stress to households, industry, power stations and irrigation schemes (Davis, 1983). There are three types of drought {Thomas, 1965): meteorological, agricultural and hydrological droughts. Meteorological drought occurs when the rainfall is abnormally low. Agricultural drought exists when the soil is depleted to the extent that crop harvests are reduced significantly (Davis, 1983). Agricultural drought has a common time scale of a season (3 to 6 months) (Harsch E, 1992). Agricultural drought can also be caused by excessive rain or flood leading to a damage of crops. Hydrological drought is associated with scarcity of precipitation on a longer time scale (1- 2 years or more) and its effect is on ground water supply (Meigh et al, 1992). Meteorological drought can be seen as a subset of agricultural drought. If there is agricultural drought then there is also meteorological drought. On the other hand, agricultural and hydrological drought can be out of phase, each having different signatures (Rouault and Richard, 2003).